Overcoming resistance to PD-1/PD-L1 inhibitors in esophageal cancer - Cheng, Chao; Zhuge, Lingdun; Xiao, Xin; Luan, Siyuan; Yuan, Yong (Frontiers in Oncology, 2022)
As the predominant treatment option of the immunotherapy for advanced esophageal cancer (EC), the application of programmed death 1 (PD-1) and programmed death-ligand 1 (PD-L1) inhibitors brings new hope to clinical practice. However, a considerable portion of patients do not response to this therapy, meanwhile most patients sensitive to PD-1 or PD-L1 antibody initially will develop resistance to the treatment eventually. To break through the limits of clinical effect, it is of critical importance to make a profound understanding of the mechanisms of so called primary resistance and acquired resistance. Subsequently, exploring potent predictors to identify suitable patients for anti-PD-1/PD-L1 treatment and investigating efficient strategies to overcome drug resistance will be helpful to expend the benefit of immunotherapy. In the present view, we summarized the potential predictive factors for anti-PD-1/PD-L1 immunotherapy in EC, and demonstrated the plausible mechanisms of resistance to PD-1/PD-L1 blockade as well as its feasible solutions.